PERAN PERBANKAN SYARIAH DALAM MEMPENGARUHI PERTUMBUHAN EKONOMI INDONESIA TAHUN 1993-2016 - Annisa Nurhasibah; Raditya Sukmana (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to determine the influence of Islamic banking, and investment on economic growth Indonesia in 1993-2016. This study uses a quantitative approach. The analysis technique used Autoregressive Distributed Lags (ARDL). This research used simple random sample. Sample that used in this research were taken from World Bank Data while for islamic banking data obtained from official website of all islamic banking in Indonesia. The result of the research shows that in the long term Islamic financing variable has a significant positive impact on the economic growth in Indonesia, while the short variable of sharia banking has a significant positive impact on the economic growth in Indonesia. Both of these proves that sharia banking has an active role to the economic growth of the country, especially in Indonesia. While the investment variables derived into variable Gross Fixed Capital Formation or GFCF have a significant negative impact on the economic growth of Indonesia in the short and long term.Keyword : Islamic Banking, Investment, Economic Growth, Indonesia, ARDLREFFERENCESAbduh, Muhamad dan Mohd Azmi Omar. 2012. Islamic Banking and Economic Growth: the Indonesian Experience. International Journal of Islamic and Middle Eastern Finance and Management, Vol. 5, No. 1.Adhikary, Bishnu Kumar. 2011. FDI, Trade Openness, Capital Formation, and Economics Growth in Bangladesh: A Lingkage Analysis. International Journal Of Business and Management , Vol. 6, No. 1.Adzhani, Rilanda dan Rini. 2017. Komparasi Kinerja Perbankan Syariah di Asia dengan Pendekatan Maqashid Syariah. Jurnal Akuntansi dan Keuangan Islam, Vol. 5, No. 1.Adzhani, Rilanda dan Rini. 2017. Komparasi Kinerja Perbankan Syariah di Asia dengan Pendekatan Maqashid Syariah. Jurnal Akuntansi dan Keuangan Islam, Vol. 5, No. 1.Ajijah, Shochrul R, dkk. 2011. Cara Cerdas Menguasai Eviews. Jakarta: Salemba Empat.Alege, Philip O. dan Henry Okuda. 2014. International Competitiveness and Growth of the Nigerian Economy: A Structural VAR-Based Perspective. Research in Applied Economics, Vol. 6, No. 4.Alimi, R. Santos. 2014. Ardl Bounds Testing Approach To Cointegration: A Reexamination of Augmented Fisher Hypothesis in an Open Economy. Asian Journal of Economic Modelling. Vol. 2(2): 103-114.Antonio, Muhammad Syafi’i. 2001. Bank Syariah dari Teori ke Praktek. Jakarta: Gema Insani Press.Arikunto, Suharsimi. 2013. Prosedur Penelitian Suatu Pendekatan Praktik. Jakarta: PT Rineka Cipta.Azam, et al. 2013. The Role of External Debt in Economic Growth of Indonesia – A Blessing or Burden. World Applied Sciences Journal., Vol. 25, No. 8.Bank Indonesia. 2005. Laporan Perkembangan Perbankan Syariah 2005. Jakarta: Bank Indonesia._____________. 2008. Laporan Perekonomian Indonesia 2008. Jakarta: Bank Indonesia._____________. 2012. Laporan Perkembangan Perbankan Syariah 2012. Jakarta: Bank Indonesia._____________. 2014. Laporan Perekonomian Indonesia 2014. Jakarta: Bank Indonesia._____________. 2016. Laporan Perekonomian Indonesia 2016. Jakarta: Bank Indonesia._____________. 2016. Metadata. Jakarta: Bank Indonesia.Bappenas. 2017. Perkembangan Ekonomi Indonesia dan Dunia Triwulan I Tahun 2017. Jakarta: Bappenas.Digdowiseiso, Kumba. 2009. Education Inequality, Economic Growth, and Income Inequality: Evidence From Indonesia 1996-2005. Munich Personal RePEc Archive MPRS Paper No. 17792 hal 213-219.Fahrani, Yadzan Gudarzi dan Masood Dastan. 2013. Analysis Of Islamic Banks’ Financing and Economic Growth: A Panel Cointegration Approach. International Journal of Islamic and Middle Eastern Finance and Management, Vol. 6, No. 2.Frensindy, Budi. 2007. Bank Based Vs Market Based. Research International BulettinGoaied, Muhamed dan Seifallah Sassi. 2010. Financial Development and Economi Growth in The MENA Region: What About Islamic BankingDevelopment.International Journal of Economics and Finance, Vol. 7, No. 3Hachicha, Nejib dan Amine Ben Amar. 2015. Does Islamic Bank Financing Contribute To Economic Growth? The Malaysian Case. International Journal Of Islamic And Middle Eastern Finance and Management, Vol. 8, No. 3Halwani, R Hendra. 2002. Ekonomi Internasional dan Globalisasi Ekonomi. Jakarta: Ghalia Indonesia.Huda, Nurul dan Muhammad Heykal. 2010. Lembaga Keuangan Islam, Tinjauan Teoritsi dan Praktis. Jakarta: Kencana.Hung, F.S., & Cothren, R. 2002. Credit Market Development and Economic Growth. Journal Of Economics and Business, Vol 54(3): 219-237.Ismail. 2010. Perbankan Syariah. Jakarta: Kencana Prenada Media Group.Mankiw, N. Gregory. 1999. Makroekonomi. Edisi Keempat. Jakarta: Erlangga.Noor, Henry Faizal. 2009. Investasi, Pengelolaan Keuangan Bisnis dan Pengembangan Ekonomi Masyarakat. Jakarta: PT Indeks.Kanu, Succes Ikechi dan Ozurumba, Benedict Anayochukwu. 2014. Capital Formation and Economics Growth in Nigeria. Global Journal Of Human Social Science: E Economics Vol. 14, No. 4.Otoritas Jasa Keuangan. 2013. Laporan Perkembangan Keuangan Syariah Tahun 2013. Jakarta: Otoritas Jasa Keuangan.Raiyandana, Ar. 2016. Analisis Pengaruh Sektor Moneter Terhadap Pertumbuhan Ekonomi di Indonesia Periode 1980-2013. Universitas Airlangga: Skripsi Tidak Diterbitkan.Rajni, Sasmiharti. 2007. Pengaruh Angkatan Kerja Dan Penanaman Modal Tetap Bruto Terhadap Pendapatan Per Kapita Propinsi di Indonesia. Jurnal Kajian Ekonomi, Vol, 5. No. 2.Rahmaddi, Rudy. 2011. Exports and Economic Growth in Indonesia: A Causality Approach based on Multi-Variate Error Correction Model. Journal of International Development and Cooperation, Vol. 17, No. 2.Samuelson, A. Paul dan Nordhaus, D. William. 1992. Ekonomi. Edisi 12 Jilid 2. Jakarta: Erlangga.Soliu, Adegboya dan Ibrahim, Odusanya. 2014. Empirical Analysis of Trade Openness, Capital Formation, FDI, and Economic Growth: Nigeria Experience. Valley International Journals. Vol. 1 No. 36-50.Sukirno, Sadono. 2010. Makroekonomi: Teori Pengantar Edisi Ketiga. Jakarta: PT Raja Grasindo Perseda.Taqwa, Khoirul Zadid. 2017. Analisis Kinerja Intermediasi Sistem Keuangan Syariah (Perbankan Syariah dan Pasar Modal Syariah) terhadap Pertumbuhan Ekonomi Indonesia Tahun 2003:Q1-2015:Q4. Skripsi tidak diterbitkan.Ugochukwu, Ugwuegbe S dan Chinyere, Uruakpa Peter. 2013 The Impact of Capital Formation on the Growth of Nigeria Economy. Research Journal of Finance and Accounting Vol. 4 No. 9.Undang-undang Perbankan Syariah. 2008. -------------------. Jakarta: Sinar Grafika.Undang-undang Perbankan. 2009. ---------------------. Jakarta: Sinar Grafika.Usman, Rachmadi. 2013. Aspek Hukum Perbankan Syariah di Indonesia. Jakarta: Sinar Grafika.Waljianah, Riza. 2013. Determinan Tingkat Suku Bunga Pinjaman Perbankan di Indonesia (Periode Juli 2005-Desember 2011). Jurnal Ilmiah.Yuksel, Serhat dan Sinemis Zengin. 2016. Cusality Relationship Between Import, Export, and Growth Rate in Developing Countries. International Journal of Commerce and Finance. Vol. 2 No. 1b. Yusof, Rosylin Mohd. dan Mejda Bahlous. 2013. Islamic Banking and Economic Growth in GCC & East Asian Countries A Panel Cointegration Alaysis. Journal Of Islamic Acounting and Business Research, Vol. 4, No. 2.